Pengaruh Demografi dan Ekonomi Terhadap Perencanaan Pelaporan Pajak Penghasilan Guru Akhir Tahun di Sekolah Dasar Yang Terdapat di Kabupaten Solok - Rita Dwi Putri; Chintya Maharani; Natasya Natasya; Tevi Putri; Marisa Penriani; Hidayanti Fitra (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to analyze the influence of demographic factors on the compliance of income tax (PPh) reporting among elementary school teachers in Padang City. Compliance with income tax reporting is crucial in supporting a sound and fair tax system. The demographic factors examined in this study include age, education level, and length of teaching. These three factors were chosen because they have the potential to influence teachers' level of understanding and awareness regarding their tax obligations. A quantitative approach was used in this study using a survey method conducted in Padang City. Data collection was conducted by distributing questionnaires to 39 respondents who were elementary school teachers in the area. The distributed questionnaires contained questions related to demographic factors and income tax reporting compliance. The collected data were then analyzed using a normality test and multiple linear regression to examine the influence of demographic factors on PPh reporting compliance. The results of the normality test showed that the data obtained were normally distributed, meaning the collected data could be used for further analysis. A multiple linear regression test was used to determine the simultaneous influence of demographic factors on PPh reporting compliance. The results of the analysis showed that demographic factors simultaneously had a significant effect on PPh reporting compliance among elementary school teachers in Padang City. This indicates that teachers' demographic characteristics, such as age, education level, and length of teaching, are closely related to their awareness of reporting income tax. Partially, the test results indicate that age and education level significantly influence compliance with income tax reporting. Older teachers tend to have a better understanding of tax obligations, while teachers with higher education levels are also more aware of the importance of reporting their taxes correctly.